Electricity nowcasting and forecasting efficiency in blockchain-integrated energy trading platforms - Ameni Boumaiza (Energy Strategy Reviews)
The rapid increase in global energy demand and the shift towards sustainable energy sources have highlighted the need for more efficient, transparent, and decentralized energy management systems. This study presents a novel blockchain-enabled marketplace designed to enhance energy trading and management through advanced nowcasting and forecasting techniques. Leveraging blockchain technology, this marketplace provides a decentralized platform for peer-to-peer energy transactions, offering greater transparency, security, and efficiency compared to traditional energy markets. Our methodology integrates real-time nowcasting algorithms and machine learning-based forecasting models to optimize electricity distribution, battery storage utilization, and cost efficiency within the marketplace. Experimental results demonstrate a substantial reduction in electricity costs for consumers by an average of 25% and a decrease in carbon dioxide (CO2) emissions by 40 tons annually. Furthermore, the system achieves an approximately 30% reduction in battery storage requirements, highlighting its potential for improving grid stability and promoting renewable energy integration. These findings underscore the transformative impact of blockchain technology on the energy sector, paving the way for sustainable and economically viable energy management solutions.